Osaka Gas Award 2005 - Universiti Malaysia Sarawak, Faculty of Engineering (Faculty of Engineering, 2005)
Osaka Gas Award 2005 had been held at Main Meeting Room in Chancellery buildings and been launched by Vice Canselor UNIMAS, Ybhg Prof. Datuk Abdul Rashid Abdullah